PERFORMA EKSPOR SEKTOR PERIKANAN ASEAN-5 - Nindya Lestari (JSEP (Journal of Social and Agricultural Economics), 2022)
This study aims to identify the export performance of the fisheries sector in ASEAN-5 countries with China's export destination. Export performance is seen based on four effects based on the Constant Market Share (CMS) analysis method by Richardson (1971), namely the growth effect, commodity effect, market effect, and competitiveness effect. The data used is the third revised SITC data from UN COMTRADE for commodity codes SITC-034, SITC-035, SITC-036, and SITC-037. Based on the calculation results, it is known that ASEAN-5 has a good growth effect. In commodity securities, Indonesia needs to diversify its products. On the market effect, ASEAN-5 is in a relatively fast-growing market, and on the competitiveness effect, only Indonesia and Thailand have strong competitiveness.